Нефтегазопромысловое оборудование: учебное пособие - Крец В. Г. Виктор Георгиевич; Саруев Л. А. Лев Алексеевич; Лукьянов В. Г. Виктор Григорьевич; Шадрина А. В. Анастасия Викторовна (Томск, Изд-во ТПУ, 2011)
Заглавие с титульного экрана